Tata Kelola Manajemen Keuangan pada Usaha Travel Syariah - Luqman Hakim; Diana Hasan; Hera Oktadiana; Muhammad Fahmi (JURNAL ABDIMAS SERAWAI, 2025)
This community service is carried out with the aim of increasing the financial management governance capacity at PT. Radisha Travel as a sharia travel business. The main problem faced by partners is that financial recording, cash flow management, and the separation of personal and company finances are not yet optimal, which has the potential to hamper strategic decision making and business sustainability. The methods used in this activity include partner situation analysis, financial management assistance, simple accounting-based recording training, and preparation of financial reports in accordance with sharia principles and applicable accounting standards. The results of the activity show an increase in partners' understanding in recording transactions, preparing monthly financial reports, as well as their ability to carry out financial planning and evaluation. Apart from that, the application of sharia principles in financial governance also provides added value for strengthening the identity of sharia travel businesses. Thus, this service program is able to make a real contribution in increasing the professionalism of PT's financial management. Radisha Travel, while supporting business sustainability and customer trust.